Photoelimination Potential of Chitosan Nanoparticles-Indocyanine Green Complex Against the Biological Activities of Acinetobacter baumannii Strains: A Preliminary In Vitro Study in Burn Wound Infections - Pourhajibagher, Maryam; Hosseini, Nava; Boluki, Ebrahim; Chiniforush, Nasim; Bahador, Abbas (Journal of Lasers in Medical Sciences, 2020)
Introduction: Acinetobacter baumannii strains are important agents causing serious nosocomial infections including soft-tissue and skin infections in patients with burn wounds which have become resistant to several classes of antibiotics. Antimicrobial photodynamic therapy (aPDT) as an alternative antimicrobial procedure is suggested for the treatment of these kinds of infections. The aim of the current study is to evaluate the antibacterial and anti-biofilm efficiency of aPDT by the utilization of an improved form of indocyanine green (ICG) which is encapsulated in chitosan nanoparticles (NCs@ICG). Methods: NCs@ICG were synthesized and confirmed by the scanning electron microscope (SEM). aPDT was performed using NCs@ICG with an 810 nm wavelength of the diode laser at the fluency of 31.2 J/cm2 on 50 A. baumannii strains isolated from burn wounds. The antibacterial and anti-biofilm potential of NCs@ICG-aPDT was determined via the colony forming unit (CFU)/mL and crystal violet assays, respectively. In addition, microbial biofilm degradation was evaluated by the SEM. Results: According to the results, NCs@ICG-aPDT showed a significant reduction of 93.2% on the CFU/mL of planktonic A. baumannii strains compared to the control group (untreated group; P < 0.05). In addition, the biofilm formation of A. baumannii strains was significantly reduced by 55.3% when the bacteria were exposed to NCs@ICG-aPDT (P < 0.05). In contrast, NCs@ICG, ICG, and the diode laser alone were not able to inhibit the CFU/mL and biofilm of A. baumannii strains (P > 0.05). Based on the results of SEM images, NCs@ICG-aPDT disrupted the biofilm structure of A. baumannii strains more than other groups. Conclusion: NCs@ICG-aPDT demonstrates a promising treatment candidate for exploitation in wound infections against both planktonic and biofilm forms of A. baumannii strains.